Comorbidity and extra pulmonary manifestations in hospitalized patients with coronavirus disease (COVID-19) depending on age and sex - Kuryata, O.V.; Semenov, V.V.; Fetkhi, S.; Frolova , Ye.O. (Medicni Perspektivi, 2024)
Nowadays, knowledge about the causal relationships between concomitant chronic diseases and the course of coronavirus infection (COVID-19) can make a huge contribution to saving the lives of patients. Determining the impact of concomitant pathology on the severity of the course of COVID-19 will contribute to the identification and assessment of the risk of deterioration of the condition, as well as the implementation of preventive measures in high-risk individuals (vaccination). The aim of the work was to assess the influence of age and sex on the presence of comorbid pathology and the course of the disease in patients who were hospitalized with community-acquired viral pneumonia associated with COVID-19. We carried out a retrospective analysis of the case histories of 260 patients with community-acquired pneumonia associated with coronavirus disease, who were treated in the therapeutic departments of the Covid Center of ME “Dnipropetrovsk regional clinical hospital named after Mechnikov” DRC in 2020-2021. (September-December 2020, January- December 2021), single-center study. All patients included in the analysis underwent general clinical and laboratory methods of research regulated by national recommendations for the management of patients with COVID-19, PCR tests (polymerase chain reaction) for verification of coronavirus disease, CT(computed tomography)/radiography of the lungs. Comorbidity was assessed as the development of the disease before the onset / verification of coronavirus disease according to a patient survey recorded in medical records. One or more comorbid conditions were recorded in 195 (75%) patients. Multimorbidity was recorded in 111 (56.9%) patients from the total number of patients with COVID-19 and comorbid pathology. Analyzing the influence of gender in patients with comorbid pathology, men were significantly more likely to have coronary artery disease (CAD) (p=0.04) and chronic obstructive pulmonary disease (COPD) (p=0.04). A significant difference in age among hospitalized patients with a diagnosis of COVID-19 was revealed, depending on sex (p<0.001). So at the age of up to 65 years, male patients predominated (60.4%), over the age of 65 years – women (68.9%). There was no significant difference in the frequency of occurrence of moderate severity and severe course of the disease of COVID-19, depending on age and sex. At the age of over 65, the presence of type 2 diabetes (p<0.001), hypertension (R<0.001), coronary artery disease (p<0.001) and COPD (p<0.001) was significantly more common.